The Effect of Authentic Leadership and Work Engagement on Job Performance: Evidence from DKI Jakarta Provincial Government - Sri Ramadhani Asda; B. Medina Nilasari (Universitas Mercu Buana, 2022)
Human Resources plays an important role in Government agencies. The Provincial Government of DKI Jakarta is trying to improve the knowledge and talents of employees with budget funds allocated for training, development, and significant improvements in both the administration and service fields to maximize the performance of Civil Servants.Objective: This study aims to analyze the effect of authentic leadership and work engagement on job performance, and High Performance Human Resource (HPHR) practices as variables that mediate the relationship between authentic leadership and work engagement on job performance.Methodology: The method used in this study is a quantitative method, using survey research with employees of the DKI Jakarta Provincial Government as the object of research. Data collection which was used is the cross-sectional method by distributing questionnaires. The research sample was selected using the purposive sampling method in order to obtain 205 respondents. The data analysis method used was Structural Equation Modeling (SEM) with AMOS 21 software. Results from the previous study were considered by adding work engagement variables in determining strategies to improve job performance.Findings: The results of this study provide information on authentic leadership participation, it will improve job performance and HPHR Practices, as well as increase an employee's attachment to work, also the more HPHR Practices and job performance will increase in the organization.Conclusion: Structuralists are expected to improve authentic leadership, especially from an internalized moral perspective, to produce ethical and transparent behavior. Civil servants need to increase work engagement, especially in the absorption aspect where employees need to concentrate fully when working in the office, develop deep interest, and willingness so that they feel bound to their work. To achieve this, a positive work environment is needed. As a result, employees feel comfortable, safe, and enthusiastic when working.